201 ETIOLOGY AND CLINICAL PRESENTATION OF MENINGITIS IN CHILDREN WITH CANCER. (1st January 2006) - Buie, K. A.; Tuomanen, E. I.; Flynn, P. M.
Abstract : Purpose: To identify the clinical symptoms and causative organisms of meningitis in children with cancer. Methods: Fifty-three patient records from SJCRH during the period of January 1, 1990 to January 1, 2000 were IRB-approved for review for the following parameters: demographics, underlying diagnosis, clinical course and treatment of the meningitis, pertinent laboratory results, and outcome. During the period of data collection, 19 patients were excluded due to lack of a cancer diagnosis or a discernable episode of meningitis or inability to obtain medical records. This resulted in 35 cases available for analysis. Patients ranged in age from 0.4 to 38.3 years, all having been diagnosed with childhood leukemia or lymphoma. Results: There were 22 episodes of bacterial meningitis, 2 episodes of fungal meningitis, and 1 episode of viral meningitis. Positive CSF cultures identified Staphylococcus aureus, Staphylococcus epidermidis, and non-pneumococcal alpha-hemolytic streptococci as the major causative organisms. Clinical information demonstrated that 30 patients had no photophobia, 28 patients had no seizure, 23 patients had no neck pain or nuchal rigidity, 21 patients had no decrease in level of consciousness, 20 patients had no nausea or vomiting, 18 patients had no headache, 10 patients had no fever, and no patients experienced hypothermia. In addition, only 12 patients were tachypnic, 15 patients were tachycardic, and 5 patients were hypotensive. Every patient in this study lacked 3 or more of these common signs or symptoms of meningitis. Conclusions: This study found that of the organisms found to be causative in our study, none were among those commonly isolated from the general population. Staphylococcus was the most frequent cause of meningitis, along with Bacillus cereus, alpha-hemolytic streptococcus, and Candida tropicalis. As for the clinical presentations observed in this study, many subjects lacked the common telltale signs of meningitis often seen in the general population. In fact, half of the patients had no headache and two-thirds had no neck pain/nuchal rigidity. Fever, the most common presenting symptom in this study and an extremely common symptom in cancer patients overall, was absent in one-third of the patients. The unusual organisms and presentations identified in this study underline the need for extreme watchfulness among treating physicians so that these infections are quickly recognized and rapidly treated.